First-rib stress fracture in two adolescent swimmers: a case report - Low, S.; Kern, M.; Atanda, A. (Journal of Sports Sciences, 2016)
First-rib stress fractures have been described in adolescent athletes in various sports, with only one prior case report of first-rib stress fractures in an adolescent female swimmer. There is a need for research on the cause, management, and prevention of these injuries as they lead to significant morbidity and critical time away from sport for these aspiring athletes. We aimed to describe first-rib stress fractures as a potential cause for non-specific atraumatic chronic shoulder pain in adolescent swimmers and to discuss the different presentations, unique risk factors, treatment, and potential injury prevention strategies of such fractures. We discussed two such cases which were successfully treated with activity modification with restriction of all overhead activity, gradually progressive physical therapy and a return to swimming protocol. First-rib stress fractures can vary in presentation and should be in the differential diagnosis in adolescent swimmers with chronic shoulder pain. These injuries can be successfully managed with rest from overhead activities and physical therapy. Gradual return to competitive swimming can be achieved even with non-union of a first-rib stress fracture. Emphasis on balanced strength training in different muscle groups and proper swimming technique is essential to prevent these injuries.